Modelling and simulation of flow and agglomeration in deep veins valves using discrete multi physics. (1st October 2017) - Ariane, M.; Wen, W.; Vigolo, D.; Brill, A.; Nash, F.G.B.; Barigou, M.; Alexiadis, A.
Abstract: The hemodynamics in flexible deep veins valves is modelled by means of discrete multi-physics and an agglomeration algorithm is implemented to account for blood accrual in the flow. Computer simulations of a number of valves typologies are carried out. The results show that the rigidity and the length of the valve leaflets play a crucial role on both mechanical stress and stagnation in the flow. Rigid and short membranes may be inefficient in preventing blood reflux, but reduce the volume of stagnant blood potentially lowering the chances of thrombosis. Additionally, we also show that in venous valves, cell agglomeration is driven by stagnation rather than mechanical stress. Highlights: Development of a discrete multi-physics model for both the blood dynamics and the leaflets mechanics in a venous valve. The model accounts for the hydrodynamics, the valve deformation with contact closure, and the solid aggregation. The key role of the flexibility and the length of the valve in both stress and flow stagnation are investigated. In venous valve, stagnation can be more important than stress in thrombus formation and propagation.